Incorporação de meios de cultivo microbiológico em compostagem - Gonçalves, Letícia (2013)
This study aimed to incorporate nutritious microbiological grown medium, along with fruit and vegetable scraps, grass clippings and leaves in the composting process, in order to verify the influence of the residue of Microbiology in the final compound. Made the use of plastic container with forced aeration, and the experiments were performed in a Preliminary and Main Study. In the main study, were incorporated poultry manure and humus to the process, aiming to increase the number of microorganisms and thus encourage the process, since there was no temperature increase in the Preliminary Study. Analyses of pH, Carbon content, temperature, aeration and moisture content for the Main Study. At the end of the process, we analyzed the nutrient content aggregated and compared this to the properties of commercial organic fertilizers such as compost and chicken manure. It was found that the application of microbiological nutrient culture media did not influence the aggregation or availability of nutrients compared to the compound coming from composting compound without the addition of grown medium. Low temperatures also obtained for the Main Study prevented sterilization of the material obtained, which prevents its application in agricultural systems. However, the final product may be applied as a soil pH correction in the process of setting, by having a pH in the range of 7.0 to 8.0 and in accordance with the amount of nutrients found can also be used as auxiliary fertilization gardening. It is concluded that the use of composting culture media is presented as an alternative for disposal of this waste, in front of its routing in landfills.